Reflections about Osteoarthritis and Curcuma longa - Akuri, Marina Cristina; Barbalho, Sandra Maria; Val, Raíssa Meira; Guiguer, Elen Landgraf (Pharmacognosy Reviews)
Osteoarthritis (OA) is a chronic inflammatory degenerative process that affects joints such as the hands, hips, shoulders, feet, spine, and especially knees in millions of people worldwide. Some authors have shown that Curcuma longa components may exhibit benefic effects in the treatment of degenerative diseases as OA. This plant belongs to the family Zingiberaceae and it is popularly known as turmeric or saffron. This review intended to perform a retrospective search to identify studies involving humans and animal models. This review was based on articles linking OA and C. longa. Databases as Medline, Science Direct, and Lilacs were consulted and a retrospective search was carried out in order to identify studies involving humans and animal models. The curcuminoids from C. longa exhibit actions at different locations in the pathogenesis of OA once it may play an important role as anti-inflammatory, down-regulating enzymes as phospholipase A2, cyclooxygenase-2, and lipoxygenases, and reducing tumor necrosis factor-alpha-and interleukins such as interleukin-1b (IL-1b), IL-6, and IL-8. They also act as inducer of apoptosis in synoviocytes, decreasing the inflammation process and may also reduce the synthesis of reactive oxygen species. For these reasons, new pharmaceutical technology and pharmacological studies should be proposed to determine the dose, the best delivery vehicle, pharmaceutical formulation and route of administration of this plant so its use as an adjunct in the treatment of OA may become a reality in clinical practice.
Keywords: Curcuma longa; curcumin; inflammation; osteoarthritis